Old Edifices, New Uses: Three Residential Buildings of a Romanian Aristocratic Family and Their Destiny after 1930 - Marin Barutcieff, Silvia (Acta historiae artis Slovenica, 2023)
The paper examines how three residential buildings, edified in Romania in medieval and early modern times by the members of the Golescu family, were repurposed during the 20th and 21st centuries, that is, before, during and after the Romanian communist period. It considers the social and political circumstances in which the analysed examples of the Golescu residential buildings have changed owners, appearance and function during the last 80 years.